Internet of things security and privacy practical and management perspectives - Awad, Ali Ismail; Ahmad, Atif; Choo, Kim-Kwang Raymond; Hakak, Saqib (CRC Press, 2023)
The Internet of Things (IoT) has emerged due to information and communication technology developments, expanding the ability to connect numerous objects.
Keywords: Internet of things; Computer security